Clinical impact of pre-admission antithrombotic therapy in hospitalized patients with COVID-19: A multicenter observational study. (September 2020) - Russo, Vincenzo; Di Maio, Marco; Attena, Emilio; Silverio, Angelo; Scudiero, Fernando; Celentani, Dario; Lodigiani, Corrado; Di Micco, Pierpaolo
Abstract: Little is still known about the clinical features associated with the occurrence of acute respiratory distress syndrome (ARDS) in hospitalized patients with Coronavirus disease 2019 (COVID-19). The aim of the present study was to describe the prevalence of pre-admission antithrombotic therapies in patients with COVID-19 and to investigate the potential association between antithrombotic therapy and ARDS, as disease clinical presentation, or in-hospital mortality. We enrolled 192 consecutive patients with laboratory-confirmed COVID-19 admitted to emergency department of five Italian hospitals. The study population was divided in two groups according to the evidence of ARDS at chest computed tomography at admission. Propensity score weighting adjusted regression analysis was performed to assess the risk ARDS at admission, and death during hospitalization, in patients treated or not with antiplatelet and anticoagulant agents. ARDS was reported in 73 cases (38 %), who showed more likely hypertension compared to those without ARDS (57.8 % vs 49.6 %; P = 0.005). Thirty-five patients (18.5 %) died during the hospitalization. Not survived COVID-19 patients showed a statistically significant increased age (77 ± 8.31 vs 65.57 ± 8.31; P = 0.001 ), hypertension (77.1 % vs 53.5 %; P = 0.018 ) and coronary artery disease prevalence (28.6 % vs 10.2 %; P = 0.009 ). Both unadjusted and adjusted regression analyses showed no difference in the risk of ARDS at admission, or death during hospitalization, between patients treated or not with antiplatelets or anticoagulants. Pre-admission antithrombotic therapy, both antiplatelet and anticoagulant, does not seem to show a protective effect in severe forms of COVID-19 with ARDS at presentation and rapidly evolving toward death.